Explore BrainMass
Share

Quadratic Equation Calculations

This content was STOLEN from BrainMass.com - View the original, and get the already-completed solution here!

Project # 1
Work only equation: (a) x^ - 2x - 13 = 0 and (c) x^ + 12x - 64 + 0, but complete all 6 steps (a-f) as shown in the example.

Project#2,
Please select at least five numbers: 0(zero), two even numbers and two odd numbers. Make sure you organize into separate projects.
The assignment must include all the math work required to answer the problems.
The steps are:
• Move the constant term to the right side of the equation.
• Multiply each term in the equation by four times the coefficient of the x^ term.
• Square the coefficient of the original x term and add it to both sides of the equation.
• Take the square root of both sides.
• Set the side of the equation equal to the positive square root of the number on the right side and solve for x.
• Set the left side of the equation equal to the negative square root of the number on the right side and solve for x.

Example: Solve x^ + 3x - 10 = 0
X^ + 3x = 10
4x^ + 12x = 40
4x^ + 12x + 9 = 40 + 9
4x^ + 12x + 9= 49
2x + 3 = + 7
2x + 3 = + 7 2x + 3 = - 7
2x = 4 2x = -10
x = 2 x = -5.

© BrainMass Inc. brainmass.com October 17, 2018, 12:05 pm ad1c9bdddf
https://brainmass.com/math/number-theory/quadratic-equation-calculations-564581

Solution Preview

Please see solution attached.

Project # 1
(a) x2-2x-13=0
4x2-8x=52
4x2-8x+4=52+4
4x2-8x+4=56
(2x-2)2=56
2x-2= 2 ...

Solution Summary

This solutions solves the quadratic equations by completing the square.

$2.19
Similar Posting

Using the quadratic formula to solve quadratic equations

Is it true that solutions to quadratic equations can always be found using the quadratic formula?

View Full Posting Details